Direct Introduction of Ethoxycarbonyldifluoromethyl‐Group to Heteroarenes with Ethyl Bromodifluoroacetate via Visible‐Light Photocatalysis. Issue 7 (19th July 2013) - Lin, Qingyu; Chu, Lingling; Qing, Feng‐Ling
Abstract A mild and versatile approach for the direct introduction of ethoxycarbonyldifluoromethyl‐group to heteroarenes via visible‐light photocatalysis has been developed. The new photoredox protocol has enabled the difluoromethylenation of heteroarenes containing a wide range of common functional groups under mild conditions.